2012
DOI: 10.1016/j.yrtph.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The ability of animal studies to detect serious post marketing adverse events is limited

Abstract: The value of animal studies to assess drug safety is unclear because many such studies are biased and have methodological shortcomings. We studied whether post-marketing serious adverse reactions to small molecule drugs could have been detected on the basis of animal study data included in drug registration files. Of 93 serious adverse reactions related to 43 small molecule drugs, only 19% were identified in animal studies as a true positive outcome, which suggests that data from animal studies are of limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 13 publications
(12 reference statements)
0
27
0
Order By: Relevance
“…Those few analyses that have been done, tend to reflect unfavourably on animal models, including the dog. In 2012, a study that expressly set out to minimise bias, showed that 63% of serious ADRs had no counterparts in animals, and less than 20% of serious ADRs had a true positive corollary in animal studies (15). Other similar examples exist for testing generally (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Those few analyses that have been done, tend to reflect unfavourably on animal models, including the dog. In 2012, a study that expressly set out to minimise bias, showed that 63% of serious ADRs had no counterparts in animals, and less than 20% of serious ADRs had a true positive corollary in animal studies (15). Other similar examples exist for testing generally (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the time, cost, and ethical concerns associated with animal models add to the limitations of their use as models of disease and screening platforms for potential therapeutics. Additionally, animal models are also limited in detecting post market adverse events [6]. Traditionally, in vitro cell culture systems have allowed for more rapid disease modeling and drug discovery studies.…”
Section: Introductionmentioning
confidence: 99%
“…By presenting an overview of EU FP-funded TA to non-human primate models for immune-mediated and neurodegenerative preclinical research performed at BPRC, we want to provide insight into these processes. By including unpublished studies in our analysis, we provide a different view on the contribution of non-human primate research to the development of new therapies as compared to an analysis of the drug registration files (9, 10). Such analyses underestimate the value of non-human primate preclinical research, as drugs that are not registered because of failure in non-human primate studies are usually not included.…”
Section: Introductionmentioning
confidence: 99%